Bread: staple or luxury ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The preparation of staple foods in African countries is still a very time-consuming job. This is particularly the case in sub-Saharan countries where millet and sorghum form the basic diet and where most grain is processed by hand. As a result of...